2011
DOI: 10.1016/j.vph.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and selective estrogen receptor modulators regulate gene and protein expression in the mesenteric arteries

Abstract: Estrogen has both beneficial and detrimental effects on the cardiovascular system. Selective estrogen receptor modulators (SERMs) exhibit partial estrogen agonist/antagonist activity in estrogen target tissues. Gene targets of estrogen and SERMs in the vasculature are not well-known. Thus, the present study tested the hypothesis that estrogens (ethinyl estradiol, estradiol benzoate, and equilin) and SERMs (tamoxifen and raloxifene) cause differential gene and protein expression in the vasculature. DNA microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Interestingly, sEH is upregulated in the mesenteric arteries of these rats (Zhao et al, 2005). Treatment with ethinyl estradiol, tamoxifen, and raloxifene in ovariectomized rats upregulates sEH mRNA expression in mesenteric arteries (Mark-Kappeler et al, 2011). sEH protein is expressed in red blood cells (Jiang et al, 2008).…”
Section: Mammalian Gene Expressionmentioning
confidence: 99%
“…Interestingly, sEH is upregulated in the mesenteric arteries of these rats (Zhao et al, 2005). Treatment with ethinyl estradiol, tamoxifen, and raloxifene in ovariectomized rats upregulates sEH mRNA expression in mesenteric arteries (Mark-Kappeler et al, 2011). sEH protein is expressed in red blood cells (Jiang et al, 2008).…”
Section: Mammalian Gene Expressionmentioning
confidence: 99%
“…; Mark‐Kappeler et al. ; Harris and Hammock ). Therefore, sEH is a susceptible gene for hypertension‐associated cardiovascular diseases (Kersten et al.…”
Section: Introductionmentioning
confidence: 99%
“…47 In this context, up-regulation of SFRP2 and SFRP4 may mediate protective effects of estradiol on the arteries. On the other hand, we have observed a down-regulation of SFRP4 in response to ethinyl estradiol and equilin in the rat mesenteric arteries, 39 in a different species, a different vascular bed, and in the absence of atherosclerosis. In contrast, LRP6 is a co-receptor for frizzled.…”
Section: Discussionmentioning
confidence: 60%
“…38 In contrast to the current data, we have shown that IGF-1 decreased in the rat mesenteric arteries in response to ethinyl estradiol. 39 Similarly, Scheidegger and coworkers 40 showed that estrogen caused a decrease in IGF-1 expression in aortic smooth muscle cells. These data thus indicate a pleiotropic effect of estrogen on IGF-1 in the vasculature.…”
Section: Discussionmentioning
confidence: 96%